2008
DOI: 10.1021/ma0715122
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation during Tensile Deformation of Polypropylene

Abstract: The process of cavitation during tensile deformation of polypropylene was studied. It was shown that in injection-molded polypropylene samples cavities appear in the center of a sample shortly before yielding. With increasing deformation the cavities change their size, number, and orientation from elongated perpendicular to parallel to deformation. The cavitation process is visible also as a rapid increase of volume of deformed material. The cavitation could be suppressed by changing internal morphology of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
205
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(216 citation statements)
references
References 62 publications
11
205
0
Order By: Relevance
“…In the author's opinion these high Poisson's ratio values have to be interpreted as scattered around 0.5, and affected by inaccuracies related to the correction of transverse deformation for long times and high temperatures. At the same time, it can not be excluded that the upper plateau could be higher than 0.5, due to non-homogeneity on a microstructural scale, already present in the materials (such as crystalline regions below the melting temperature [1] or porosity [28]) or developed during the deformational process (as cavitational effects [29][30][31][32], although these should have major importance at deformations higher than those investigated here). The decrease of stress was simultaneously monitored, permitting an evaluation of the time evolution of the relaxation modulus E REL , which is reported in Figure 11b in terms of isothermal curves for an axial deformation !…”
Section: Constant Deformation Testsmentioning
confidence: 77%
“…In the author's opinion these high Poisson's ratio values have to be interpreted as scattered around 0.5, and affected by inaccuracies related to the correction of transverse deformation for long times and high temperatures. At the same time, it can not be excluded that the upper plateau could be higher than 0.5, due to non-homogeneity on a microstructural scale, already present in the materials (such as crystalline regions below the melting temperature [1] or porosity [28]) or developed during the deformational process (as cavitational effects [29][30][31][32], although these should have major importance at deformations higher than those investigated here). The decrease of stress was simultaneously monitored, permitting an evaluation of the time evolution of the relaxation modulus E REL , which is reported in Figure 11b in terms of isothermal curves for an axial deformation !…”
Section: Constant Deformation Testsmentioning
confidence: 77%
“…G'Sell et al 22 , Pawlak et al 10 and Na and Lv 19 observed that the volume of deformed polypropylene substantially increases with increasing strain. According to Bucknall's proposition for similar behavior of amorphous polymers 24 the overall volume variation is the sum of three components: elastic, plastic and cavitational.…”
Section: Introductionmentioning
confidence: 98%
“…Plastic deformation of crystalline and amorphous phases in polypropylene is often accompanied by the formation of cavities [1][2][3][4][5][6][7][8][9][10] . Cavitation process is then initiated in tensile drawing shortly before or at the yield point 11 if the resilience of the amorphous phase is lower than the strength of crystals 3,9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pawlak and Galeski [23] compared the cavitation behavior of PP with similar crystallinity and crystal thickness but different molecular masses of 400 and 250 kg/mol. They found that the samples having lower molecular weight showed stronger cavitation as a result of reduced number of entanglements in the amorphous phase.…”
Section: Role Of the State Of Amorphous Phasementioning
confidence: 99%